Assessing patient experience with patient safety in primary care: development and validation of the ASK-ME-questionnaire. Issue 4 (6th April 2022) - Stahl, Katja; Reisinger, Anna; Groene, Oliver
Abstract : Objective: To develop and test the validity and reliability of a tool measuring patient experiences with patient safety in ambulatory care that is suitable for routine use in general practitioner and specialist practices. Design: Instrument development was based on a literature review, a 3-round Delphi survey with a multidisciplinary expert panel and cognitive interviews with patients. The instrument was piloted in 22 practices using a cross-sectional survey. Exploratory (EFA) and confirmatory factor analysis (CFA) were performed to test construct validity. Internal consistency and the ability of the questionnaire to differentiate between selected subgroups and at the level of individual practices was examined. Setting: General practitioner and specialist practices. Participants: Patients aged >18 years seeking care in ambulatory care practices between February and June 2020. Results: The final ASK-ME-questionnaire consisted of 22 items covering 5 theoretical dimensions. A total of 3042 patients (71.1%) completed the questionnaire. Median item non-response rate was 4.2% (IQR 3.4%–4.7%). EFA yielded 3 factors comprising 14 items explaining 64.8% of the variance representing contributing factors to patient safety incidents. CFA confirmed the factorial structure suggested by EFA. The model fit the data satisfactorily (comparative fit index=0.92, root mean square error of approximation=0.08, standardised root mean square residual=0.08). Internal consistency values ranged from 0.7 to 0.9. Discriminant validity was supported by significant differences between patients of different age and differences in self-reported health status. The factors distinguished well between practices. Conclusion: The ASK-ME-questionnaire showed good psychometric properties. It is suitable for routine use in patient safety measurement and improvement systems in ambulatory care. Further research is required to adequately assess number and type of experienced events in routine measurements.